PROPOSAL TO DESIGNATE STRAIN ATCC 3004 (IMRU 3004) AS THE NEOTYPE STRAIN OF STREPTOMYCES ALBUS (ROSSI-DORIA) WAKSMAN AND HENRICI - Lyons, A. J. (1962)
Lyons, A. J., Jr. (Northern Regional Research Laboratory, Peoria, Ill.) and T. G. Pridham. Proposal to designate strain ATCC 3004 (IMRU 3004) as the neotype strain of Streptomyces albus (Rossi-Doria) Waksman and Henrici. J. Bacteriol. 83:370–380. 1962.—It is proposed that strain ATCC 3004 (IMRU 3004) be designated henceforth as the neotype strain of Streptomyces albus (Rossi-Doria) Waksman and Henrici and as the type strain of the genus Streptomyces Waksman and Henrici. The proposal is based not only on the fact that the holotype strain [Streptotrix (sic) alba] of Rossi-Doria is no longer extant, but also on the fact that a study of the literature and a taxonomic study of 55 strains of the organism indicate the species should exhibit these characteristics: catenulate ovoidal spores, white aerial mycelium, coiled sporophores, proteolytic activity, and nonchromogenicity (inability to form brown, deep brown, or black diffusible pigments). Strain ATCC 3004 (IMRU 3004) exhibits these characteristics, as do 16 other acquisitions. Study of the 16 additional strains that conform with the general definition of the species shows differences in some physiological characteristics. It is suggested that these differences are of subspecific significance.